PENDAMPINGDA SUAMI YANG DI TINGGALKAN ISTRI AN KONSELING PASTORAL KEPA - Monadeby Wogono; Rifke Alfione Pananggung; Frisca Elisabeth Londo (MATHESI: Jurnal Pendidikan dan Bimbingan Konseling, 2026)
The phenomenon of a husband being abandoned by his wife without clarity is a complex issue that rarely receives attention, despite having a significant impact on the lives of individuals and families. This condition is known as ambiguous loss, a loss without certainty that causes emotional confusion and difficulty in the adaptation process. This study aims to understand the impact experienced by abandoned husbands and to examine the role of pastoral counseling assistance in supporting the recovery process. This study employs a qualitative approach with a field research design. Data were collected through semi-structured interviews and observation of the research subjects. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the impacts experienced encompass psychological, social, and economic dimensions. Psychologically, the subject experienced anxiety, grief, confusion, and a tendency toward mild depression. Social impacts were reflected in changes in relationships with the surrounding environment and the emergence of dual roles within the family, while economic impacts were marked by a decline in work productivity. In addition, the child also experienced emotional disturbances due to the loss of the mother figure. Pastoral counseling assistance has proven to play an important role in helping individuals cope with such conditions through a holistic approach that encompasses emotional, relational, and spiritual dimensions. By employing client-centered and rational-emotive approaches, pastoral counseling is able to help counselees manage their emotions, develop more rational thinking patterns, and rediscover the meaning of life amid uncertainty.